De novo mammalian prion synthesis - Benetti, Federico (Landes Bioscience, 2009)
Prions are responsible for a heterogeneous group of fatal neurodegenerative diseases. They can be sporadic, genetic, or infectious disorders involving post-translational modifications of the cellular prion protein (PrP(C)). Prions (PrP(Sc)) are characterized by their infectious property and intrinsic ability to convert the physiological PrP(C) into the pathological form, acting as a template. The “protein-only” hypothesis, postulated by Stanley B. Prusiner, implies the possibility to generate de novo prions in vivo and in vitro. Here we describe major milestones towards proving this hypothesis, taking into account physiological environment/s, biochemical properties and interactors of the PrP(C).